Hubungan antara Sibling Relationship dengan Academic Performance pada Mahasiswa - Murti, Heru Astikasari Setya; Pandoi, Mariana Medelin Valera (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to examine the relationship between sibling relationships and academic performance in university students. Sibling relationships involve social, emotional, and cognitive interactions between siblings that can influence various aspects of life, including academic achievement. This research employs a correlational quantitative approach, involving 380 university students who have siblings. Data collection was conducted using the Lifespan Sibling Relationship Scale (LSRS) questionnaire and academic data based on the Cumulative Grade Point Average (GPA). Data analysis using the Spearman Rho test indicated no significant relationship between sibling relationships and academic performance (r = 0.009, p > 0.05). The findings suggest that the quality of sibling relationships does not have a significant impact on students' academic performance. These results provide insight that, although sibling relationships may contribute to emotional and social development, external factors have a greater influence on academic performance. A recommended suggestion is to explore other dominant factors that more significantly affect students' academic performance.